2018
DOI: 10.1038/s41598-017-18827-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new Pm2 allele associated with broad-spectrum powdery mildew resistance in wheat line Subtil

Abstract: Wheat powdery mildew is a severe disease affecting yield and quality. Host resistance was proved to be effective and environment-friendly. Wheat line Subtil is an elite germplasm resource resistant to 28 of 30 tested Bgt isolates. Genetic analysis showed that the powdery mildew resistance in Subtil was conferred by a single dominant gene, temporarily designated PmSub. Using bulked segregant analysis, PmSub was mapped to chromosome arm 5DS, and flanked by the markers Bwm16 and Cfd81/Bwm21 at 5.0 and 0.9 cM, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Although this locus has been cloned by mutant chromosome sequencing (Sánchez-Martín et al, 2016) and analysis of the annotated genes in the mapping interval using the reference genome of Chinese Spring , no transgenic evidence was provided to confirm that the cloned sequence is the unique functional element conferring resistance to powdery mildew. Additionally, other reports showed that all the homologous sequences in different Pm2 allele donors have the exactly the same sequence, yet these Pm2 alleles exhibit significantly different resistance spectra that cannot be explained by the background differences of the resistant germplasms (Jin et al, 2018;Ma et al, 2018). In this study, the marker order across the PmJM23 interval showed inversion and recombination phenomena (Figure 2 and Table 3).…”
Section: Discussionsupporting
confidence: 52%
“…Although this locus has been cloned by mutant chromosome sequencing (Sánchez-Martín et al, 2016) and analysis of the annotated genes in the mapping interval using the reference genome of Chinese Spring , no transgenic evidence was provided to confirm that the cloned sequence is the unique functional element conferring resistance to powdery mildew. Additionally, other reports showed that all the homologous sequences in different Pm2 allele donors have the exactly the same sequence, yet these Pm2 alleles exhibit significantly different resistance spectra that cannot be explained by the background differences of the resistant germplasms (Jin et al, 2018;Ma et al, 2018). In this study, the marker order across the PmJM23 interval showed inversion and recombination phenomena (Figure 2 and Table 3).…”
Section: Discussionsupporting
confidence: 52%
“…in Jimai 23. In our previous reports, a series of Pm2 alleles with different reaction patterns to Bgt isolates have been identified in various wheat genotypes (Ma et al, 2014(Ma et al, , 2015a(Ma et al, ,b,c, 2016(Ma et al, , 2018Xu et al, 2015;Jin et al, 2018). However, these Pm2 alleles were only characterized at the genetic level.…”
Section: Discussionmentioning
confidence: 99%
“…Even though a Pm2-related gene was cloned using mutant chromosome sequencing and candidate gene analysis using the reference genome of Chinese Spring (Sánchez-Martín et al, 2016;Chen et al, 2019), there are still aspects of this locus that require further investigation. For instance, while the homologous sequences of different Pm2 alleles are identical to each other, these alleles have significantly different reaction patterns to Bgt isolates with different virulence spectra, something which cannot be explained by the background difference of the wheat genotypes (Jin et al, 2018;Ma et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…tritici and P. triticina, respectively. To date, more than 77 formal Pm genes and more than 30 temporarily designated genes (such as PmYB or PmWFJ) have been identified in 56 chromosomal loci in bread wheat [12,13]. Most Pm genes are localized on the chromosomes of A-and B-genomes (46.2% and 35.1% of all Pm genes, respectively).…”
Section: Introductionmentioning
confidence: 99%